1992
DOI: 10.1139/e92-068
|View full text |Cite
|
Sign up to set email alerts
|

Geochronometry of the Eagle Plutonic Complex and the Coquihalla area, southwestern British Columbia

Abstract: New U–Pb, K–Ar, and Rb–Sr dates from the Eagle Plutonic Complex and adjacent map units place timing constraints on intrusive and deformational events along the southwestern margin of the Intermontane Belt. U–Pb zircon minimum dates for Eagle tonalite and gneiss (148 ± 6, 156 ± 4, and 157 ± 4 Ma) document previously unrecognized Middle to Late Jurassic magmatism and syn-intrusive deformation along the eastern margin of the Eagle Plutonic Complex and the southwestern margin of the Intermontane terrane. Widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…The field relations and structural setting described herein provide the framework for interpreting the geochronometry reported in Greig et al (1992). That the field relations are in agreement with geochronometric and other data demonstrates that the Eagle Plutonic Complex provides an excellent example of the use of plutons to date regional deformation (cf.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The field relations and structural setting described herein provide the framework for interpreting the geochronometry reported in Greig et al (1992). That the field relations are in agreement with geochronometric and other data demonstrates that the Eagle Plutonic Complex provides an excellent example of the use of plutons to date regional deformation (cf.…”
supporting
confidence: 66%
“…Camsell proposed the name "Eagle granodiorite" for plutonic rocks in the Britton (formerly Eagle) Creek valley, near the confluence with Illal Creek. His "type" locality, however, is a Late Paleocene or Early Eocene granodiorite stock (Greig 19896;Greig et al 1992). Cairnes (1924) first noted compositional variety within Eagle plutonic rocks, such as muscovite-rich varieties and pegmatites, and more mafic granitic rocks along the western flank of the Eagle Complex.…”
Section: Previous Workmentioning
confidence: 99%
“…In Washington state, the western Okanogan Range is bounded by the Pasayten fault to the west and includes Jurassic and Cretaceous plutons (including the Similkameen pluton; Petö 1974) that range in age from 166 to 154 Ma (Rb-Sr dates, consistent with K-Ar dates; Petö and Armstrong 1976) and from 114 to 110 Ma (U-Pb dates; Grieg et al 1992;Hurlow 1993). Hurlow and Nelson (1993) concluded that the 114-110 Ma plutons of the Okanogan Range represent an older, southerly segment of the late Albian volcanic rocks of the Spences Bridge Group in British Columbia, and defined the Okanogan -Spences Bridge arc as a >300 km long northnorthwest-trending Early Cretaceous magmatic arc intruded into the western margin of the Intermontane superterrane.…”
Section: Provenance Of East-derived Methow Stratamentioning
confidence: 99%
“…Alternatively, sinistral oblique motion on the Pasayten fault has been interpreted as transpressional along a steeply dipping reverse fault (Grieg 1992). Grieg et al (1992) suggest that the ductile strain in the 110.5 ± 2 Ma Fallslake plutonic suite of the Eagle Plutonic complex in southern British Columbia developed during sinistral, east-side-up reverse displacement, with northeast-dipping foliation indicating a northeast-dipping orientation for the Pasayten fault during transpressional ductile shear.…”
Section: Tectonic Implications Of Methow Provenancementioning
confidence: 99%
“…The southern Canadian Cordillera includes Mississippian to Jurassic oceanic mélange of the Cache Creek terrane, Triassic to Jurassic volcanic arc assemblages of Quesnellia, late Paleozoic oceanic rocks of the Slide Mountain terrane, and pericratonic rocks of the Kootenay terrane (Monger et al, 1982). These terranes are intruded by an extensive suite of Late Triassic to early Tertiary plutonic rocks; major pulses of magmatism occurred in Late Triassic-Early Jurassic (210-187 Ma), Middle to Late Jurassic (180-148 Ma), and middle to Late Cretaceous (130-85 Ma) time (Armstrong et al, 1988;Greig et al, 1992;Woodsworth et al, 1992;Ghosh et al, 1995).…”
Section: Potential Source Regionsmentioning
confidence: 99%